2021
DOI: 10.1002/ente.202000918
|View full text |Cite
|
Sign up to set email alerts
|

Low‐Cost Carbon Xerogels Derived from Phenol–Formaldehyde Resin for Organic Electric Double‐Layer Capacitors

Abstract: In this study, low‐cost carbon xerogels (CXs) are successfully prepared by condensation of phenol and formaldehyde and applied to electrode materials for organic electric double‐layer capacitors (EDLCs). Condensation of resorcinol and formaldehyde is the most commonly used method for the synthesis of CXs because although resorcinol is more expensive than phenol, it has better reactivity with formaldehyde. For this reason, research on the synthesis of CXs derived from phenol–formaldehyde resin is potentially us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
0
10
2
Order By: Relevance
“…The mass-normalized surface area A sum was determined to be around 926 m 2 g −1 on average with a maximum of 1004 m 2 g −1 for CXG 500 and a minimum of 894 m 2 g −1 for CXG 1000 . The surface area of all CXG 500–10,000 samples were higher than some values reported in other investigations (300–700 m 2 g −1 ) [ 34 , 41 , 42 , 45 ]. Moreover, the overall pore volume V sum of 0.2–1.0 cm 3 g −1 was similar to values referred to in the literature [ 34 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 63%
See 2 more Smart Citations
“…The mass-normalized surface area A sum was determined to be around 926 m 2 g −1 on average with a maximum of 1004 m 2 g −1 for CXG 500 and a minimum of 894 m 2 g −1 for CXG 1000 . The surface area of all CXG 500–10,000 samples were higher than some values reported in other investigations (300–700 m 2 g −1 ) [ 34 , 41 , 42 , 45 ]. Moreover, the overall pore volume V sum of 0.2–1.0 cm 3 g −1 was similar to values referred to in the literature [ 34 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 63%
“…The surface area of all CXG 500–10,000 samples were higher than some values reported in other investigations (300–700 m 2 g −1 ) [ 34 , 41 , 42 , 45 ]. Moreover, the overall pore volume V sum of 0.2–1.0 cm 3 g −1 was similar to values referred to in the literature [ 34 , 41 , 42 ].…”
Section: Resultscontrasting
confidence: 63%
See 1 more Smart Citation
“…Hence, supercapacitors have received attention in fields requiring high power densities, and many studies reported the development of carbon materials that facilitated high electrochemical performance of the supercapacitors. [123][124][125][126][127][128][129] Activated carbon materials, [123,124] carbon aerogels (or xerogels), [124][125][126] and nanocarbon materials such as carbon nanotubes, graphene, and carbon nanohorns [127][128][129] represent carbon electrode materials for supercapacitors. Recent studies involving waste-derived carbon materials for supercapacitor electrodes have attracted increasing environmental interest, [10,19,27,30,34,38,89,[130][131][132][133] and waste plastics are receiving attentions as candidate precursors for supercapacitor electrodes.…”
Section: Supercapacitorsmentioning
confidence: 99%
“…Carbon gels possess predominant properties as a controllable pore structure with a high porosity, low electrical resistivity as well as a high machinability. 2 These outstanding properties provide a remarkable potential for the design and tailoring of this material for specic applications such as electric double-layer capacitors, [3][4][5] lithium-ion batteries, [6][7][8] electrodes for fuel cells, [9][10][11] catalyst supports, [12][13][14] gas adsorption, [15][16][17] and water treatment. [18][19][20] Pekala and co-workers [21][22][23] were the rst to prepare organic gels which can be used as the precursor for carbon gels by applying the sol-gel method in 1989.…”
Section: Introductionmentioning
confidence: 99%